6x+4=-92

Simple and best practice solution for 6x+4=-92 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+4=-92 equation:


Simplifying
6x + 4 = -92

Reorder the terms:
4 + 6x = -92

Solving
4 + 6x = -92

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 6x = -92 + -4

Combine like terms: 4 + -4 = 0
0 + 6x = -92 + -4
6x = -92 + -4

Combine like terms: -92 + -4 = -96
6x = -96

Divide each side by '6'.
x = -16

Simplifying
x = -16

See similar equations:

| x^4-60+2x^2=-2x^4-x^2 | | 23=3w+4w | | 5(2d+3)=45 | | 5x+14=79 | | 4+9=2 | | 4(3)-3n=12 | | 6c-13d-9c+5d= | | x^2+Y^2-6x+4y+13=0 | | 1 = q2 | | 18y-22=3x-2 | | 12x-3x*2=0 | | 12r+s+18r+19s= | | 3v-4=3v+7 | | 11x-(7+5x)= | | 17x-8=81 | | -8(5r+1)=32 | | (-8x+2)+(-10x-7)= | | 2x-31=3(x-2) | | X^2+(6k+4)X+3=0 | | 6+30x=20x+24 | | 48*64=12x*16x | | 50-3s=2 | | 8k+2=15k-12 | | -5(7+7x)=245 | | 8k+8=17k-19 | | 10k+11=14k-9 | | 7y=y+48 | | 13=1+6x+6 | | 18*18=24x*6x | | t^2=-10t+11 | | 12*12=16x*4x | | -3(8x-1)=2x-5 |

Equations solver categories